2022
DOI: 10.3390/ijerph19127217
|View full text |Cite
|
Sign up to set email alerts
|

“It’s a Living Experience”: Bereavement by Suicide in Later Life

Abstract: Bereavement by suicide for people in later life is significantly under-researched. Research on ageing and suicide has yet to address the experiences of those bereaved by suicide and how such a devastating loss affects the ageing experience. Objectives: We explored the substantive issues involved in bereavement by suicide and its impact on later life. Methods: This was a co-produced qualitative study. Peer researchers with lived experience conducted in-depth interviews with twenty-four people aged 60–92 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Further complexity involving ethical considerations may occur, for example, where there are advanced directives and/or mental capacity in death-hastening behavior (Wax et al, 2018 ; Trowse, 2020 ; Hafford-Letchfield et al, 2022b ). Wand et al ( 2018 ) suggested that self-neglect should be conceptualized as a defensive behavior that has maladaptive outcomes and can also be associated with attempts to regain control over personal freedom and/or living arrangements, or in response to threats to self-identity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Further complexity involving ethical considerations may occur, for example, where there are advanced directives and/or mental capacity in death-hastening behavior (Wax et al, 2018 ; Trowse, 2020 ; Hafford-Letchfield et al, 2022b ). Wand et al ( 2018 ) suggested that self-neglect should be conceptualized as a defensive behavior that has maladaptive outcomes and can also be associated with attempts to regain control over personal freedom and/or living arrangements, or in response to threats to self-identity.…”
Section: Discussionmentioning
confidence: 99%
“…These self-perceptions were evident in the “throwaway” comments our participants referred to in their peer networks (e.g., “I'm ready to go now” or “my time is up”). Such statements highlight the further need for compassion and high-quality care that pays attention to the nuancing or tailoring of mainstream suicide prevention and mental health therapies for people in later life (Hafford-Letchfield et al, 2022a , b ). Validated screening tools used in suicidality with older people tend not to address these wider issues (Gleeson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations